Ricœur Before the ‘Hermeneutical Turn’: Two Works on the Early Ricœur Ricœur at the Limits of Philosophy: God, Creation, and Evil, Barnabas Aspray, Cambridge University Press, 2022 (ISBN 978-1-009-18674-2), x + 254 pp., hb £75 A Companion to Ricœur's The Symbolism of Evil, (ed.), Lexington Books, 2020 (ISBN 978-1-4985-8714-3), xx + 226 pp., hb £73 - Best, Jonathan (Reviews in religion and theology, 2024)
This review article explores two recent works on Paul Ricœur, A Companion to Ricoeur's The Symbolism of Evil, edited by Scott Davidson, and Ricœur at the Limits of Philosophy: God, Creation, and Evil by Barnabas Aspray. Both works focus on Ricœur's early works, before the ‘hermeneutical turn’. In this review, I show how both works demonstrate Ricœur's applicability to contemporary theological thought, especially concerning the symbols of creation and evil. Ultimately, both works show the depth and complexity of Ricœur's early work and his continued importance for understanding how the symbols of creation, existence, finitude and God are deep and multifaceted.